Concurso de pessoas no direito penal contemporaneo - Marques, Fernando Tadeu (2012)
The present work has as its object the studying the concourse of people, whereby, it is responsibility of each individual in criminal cases. There will be a foray into the criminal law by checking the evolution of this institute and the theories that over time seek to delimit and define the concepts surrounding the authorship and participation and the criteria for assignment of the respective responsibilities of each agent contributing towards the offense. Ahead is the analysis of the institute in its various angles, from Philippine s ordinations to contemporary documents. After delineating the object of labor it, will be analyzed early theories surrounding the subject, coming finally to domain theory of the fact and the consequences of its adoption, and there is the influence on the analysis of crime and therefore the services of people to questions posed by modern studies involving neutral actions and responsibility for the power structure